LC-MS based analysis reveal antimicrobial compounds from Gabonese pharmacopoeia: chemical characterisation and cytotoxicity evaluation - Otogo N’nang, Elvis; Essone, Paulin N.; Ella Ndong, Judicael; Boueya, Augustin; Kokou, Kossiwa; Kriz, Richard; N’nengué, Marie Andrée; Ovono Abessolo, Félix; Lell, Bertrand; Kremsner, Peter G.; Agnandji, Selidji T. (Frontiers in Natural Products, 2025)
Plants used in traditional medicine represent an important source of new compounds. Hallea ledermannii (H. ledermannii) (Krause) Verdc. (Rubiaceae), Gossypium barbadense (G. barbadense) (Malvaceae), Pycnanthus angolensis (P. angolensis) (Myristicaceae), Drypetes gossweileri (D. gossweileri) S. Moore (Euphorbiaceae) and Scyphocephalium ochocoa (S. ochocoa) Warb (Myristicaceae) are five plants widely used in traditional Gabonese medicine as antimicrobials. However, little is known about the active compounds associated with their biological activities. Based on botanical studies and the claims of traditional healers regarding the antimicrobial effects of these plants, a study to evaluate the antimicrobial activity and phyto-chemical profile of aqueous extracts of three plants (bark of H. ledermannii, G. barbadense root bark and P. angolensis bark) and methanolic extracts of two plants (S. ochocoa stem bark and D. gossweileri root bark). Under the guidance of LC-MS detection, identified twenty seven (27) potentially active compounds. Eight (8) of these belong to the quinovic acid-type triterpenoid sap-onins identified in the aqueous extract of H. ledermannii, eleven (11) are dibenzofurans, chroman and stigmasterol detected in the methanolic extract of S. ochocoa and eight(8) compounds in the methanolic extract of D. gossweileri are friedelin, drypemolundein B and gossweilone, to name but a few. In parallel, the five extracts were tested on reference bacterial strains: Staphylococcus aureus ATCC 25923, Pseudomonas aeruginosa ATCC 278533, Salmonella thyphi ATCC 13311, Klebsiella pneumoniae ATCC 700603, Shigella flexneri ATCC 24570. Three of these extracts (aqueous extract of H.ledermannii and two methanolic extracts of S. ochocoa stem bark and D. gossweileri root bark) showed moderate activity against Staphylococcus aureus ATCC 25923, with inhibition zones of12,3 ± 0,5 mm , 10,1 ± 0,5 mm and 7,6 ± 0 mm respectively. In addition, we assessed the toxicity of the three extracts that showed antimicrobial activity using an invertebrate model, Galleria mellonella (GM). We found that the LD varied according to the concentration of the plant material. The aqueous extract and the methanolic extracts were not toxic to Galleria mellonella. The LD50s (mg/ml) obtained were 93.2 mg/ml (717.2 g/kg body weight (bw)) and 100 mg/ml (762.3 g/kg bw), 95.4 mg/ml (721.1g/kg body weight (bw)).